KAJIAN PERLINDUNGAN HUKUM PADA PEMEGANG RAHASIA DAGANG - Sufiati, Dian (MAJALAH ILMIAH WIDYA, 2012)
The law No. 30 of 2000 enacted by the fever Deman mount is aimed to five law protection toward trade secret. Trade secret is one part of Intellectual property which consists of information that is unknown by public in the field of technology and or business, having economic value become it is useful in a business activity and its confidentiality should be by trade secret owner. The objective of this article is to discuss the law protection towards the trade secret owner. The method used library research and analyzed descriptively. It can be concluded that the Trade secret owner has a right to use her/his trade secret and to five a license for or to forbid another party to use expose trade secret to the third party for commercial purposes. Trade secret does not need registration because this right is from the country.